2014
DOI: 10.1111/febs.12911
|View full text |Cite
|
Sign up to set email alerts
|

The newly characterized Pl‐jun is specifically expressed in skeletogenic cells of the Paracentrotus lividus sea urchin embryo

Abstract: Growing evidence suggests that the transcription factors belonging to the Jun family are involved in many important cellular events, such as the control of bone development in mammalians. We have characterized, for the first time, a member of the Jun family from embryos of the sea urchin Paracentrotus lividus. The Pl‐jun protein sequence includes all the functional domains characteristic of members of the Jun family (i.e. the basic leucine zipper, the basic DNA‐binding and the c‐Jun N‐terminal kinase docking‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…2E, I). As showed by Russo et al (2014b), few ectoderm and endoderm cells were p-jun-positive, as indicated by arrows and arrowhead both in control (Fig. 2B) and in irradiated embryos (Fig.…”
Section: Pathways Activated By Uvrmentioning
confidence: 58%
See 4 more Smart Citations
“…2E, I). As showed by Russo et al (2014b), few ectoderm and endoderm cells were p-jun-positive, as indicated by arrows and arrowhead both in control (Fig. 2B) and in irradiated embryos (Fig.…”
Section: Pathways Activated By Uvrmentioning
confidence: 58%
“…The phosphorylated form of jun has been detected in the nuclei of some skeletogenic cells (Russo et al, 2014b), as shown in Fig. 2B, C. Indeed, p-jun co-localized with the skeletogenic cell surface marker WGA (Fig.…”
Section: Pathways Activated By Uvrmentioning
confidence: 64%
See 3 more Smart Citations